Chemical composition and biological activities of essential oils from six lamiaceae folk medicinal plants - Sun, Jiahui; Sun, Peipei; Kang, Chuanzhi; Zhang, Lanyue; Guo, Lanping; Kou, Yaping (Frontiers in Plant Science, 2022)
Essential oils have attracted wide attention in recent years due to their extensive applications in natural functional ingredients, pharmaceutical preparations, biomedical products, and the cosmetics industry. In this study, the chemical compositions and biological activities of essential oils extracted from six Lamiaceae herbs, including Pogostemon cablin (Blanco) Benth. (PCEO), Perilla frutescens (L.) Britton (PFEO), Salvia japonica Thunb. (SJEO), Rosmarinus officinalis L. (ROEO), Lavandula angustifolia Mill. (LAEO), and Agastache rugosa (Fisch. & C. A. Mey.) Kuntze (AREO), were determined and analyzed. A total of 167 components were identified from the six essential oils by GC-MS analysis, with 35, 24, 47, 46, 54, and 37 components in PCEO, PFEO, SJEO, ROEO, LAEO, and AREO, respectively. Hierarchical cluster analysis of chemical compositions showed that the composition of the six essential oils was significantly different in content, and they were clearly divided into six classes. However, all of these six essential oils exhibited promising anti-inflammatory activity by inhibiting the expression of interleukin-1, interleukin-6, tumor necrosis factor-α, and cyclooxygenase-2 in rats with adjuvant arthritis, among which PFEO had the best performance. In addition, the six essential oils displayed significant cytotoxicity on B16 (IC50 = 86.91–228.91 μg/mL) and LNCaP cell lines (IC50 = 116.4–189.63 μg/mL). Meanwhile, all of them presented satisfactory antioxidant activity (IC50 = 4.88–13.89 μg/mL) compared with Trolox C (IC50 = 13.83 μg/mL), and SJEO (IC50 = 7.93 μg/mL) served as an optimal candidate natural antioxidant by DPPH assay. Taken together, these results indicate that the six Lamiaceae essential oils manifest excellent and diverse biological activities, enabling them to be used as perfect natural functional ingredients in antioxidant, antitumor, or anti-arthritic drugs. This study provides more references for pharmaphylogeny research and drug discovery from folk medicinal plants.